Security in the Internet of Things: A Review - Diyorbek Umidjon ugli Jurayev (Zien Journals, 2022)
The aim of the research is to study the impact of global machine-to-machine interaction on the technological safety and stability of the life support systems of modern society. The article discusses the most likely threats to the violation of confidentiality, availability and integrity of information circulating in information networks that are designed to manage industrial facilities.
Keywords: Internet of things; security; communication technologies; protection